Determining First Aid Knowledge and Skills Retention with Laypeople: A Randomized Controlled Trial in Nepal (International Journal of First Aid Education)
Background: First aid (FA) education is important in building a resilient society. Millions of people are trained annually in FA worldwide. However, the knowledge concerning retention of FA and optimal retraining frequency is limited. The aims of the current study were to investigate the two-year retention of FA knowledge and skills, and to determine to what extent refresher courses with different contents after one year influence retention. Results: FA theoretical knowledge and practical skills decreased significantly over time. Attending an active refresher course after one year was associated with a lesser decay in non-resuscitative FA knowledge (p=0.04), while no effect could be shown on the retention of practical skills for bleeding (p=0.52). Surprisingly, retention of practical skills for fractures was decreased in the group that was refreshed for this skill (p=0.006). An exploratory analysis on practical CPR skills, comparing participants who participated in the refresher courses and those who did not, showed that those following a refresher had better skills retention over time (p=0.023). Conclusion: Retention in non-resuscitative FA knowledge, and resuscitative and non-resuscitative practical skills, decreases over two years. A refresher after one year seems to have modest effects on non-resuscitative FA knowledge and practical CPR skills. These results support providing annual refreshers.